PEMASARAN MELALUI MEDIA SOSIAL PADA BISNIS KULINER - Djakasaputra, Arifin; Refaldy, Alvin; Chandra, Jimmy (Transpublika Publisher, 2022)
Social Media Marketing is described as a form of Internet marketing that utilizes social media as a marketing tool whereby users produce and share content to help businesses enhance their brand experience and expand their customer reach. The purpose of the activity is to help business owners have the provision of knowledge about the importance of understanding marketing strategies through social media, in increasing sales and facing increasingly tough competition. SMEs as Partners who are the venue for activities are the Philosopia Pastry culinary business in Jambi engaged in the field of pastry business under the Pastry Philosopia brand. Based on initial observations online with zoom meetings, partners do not understand social media marketing, as a medium that is a partner's product communication to consumers without large costs. The method offered in the activity is training/socialization on a basic understanding of marketing and social media marketing, the types and benefits of social media marketing. The results of the activity show that partners have acquired the provision of knowledge about the use of social media in marketing products and can introduce products to a wider market.